2014
DOI: 10.1590/s1677-5538.ibju.2014.02.15
|View full text |Cite
|
Sign up to set email alerts
|

Obesity may influence the relationship between sex hormones and lower urinary tract symptoms

Abstract: ARTICLE INFO ______________________________________________________________ ______________________Purpose: The effects of serum testosterone in the lower urinary tract symptoms (LUTS) in patients with benign prostatic hyperplasia (BPH) are not well established. The objective of the study is to evaluate the association of sex hormones with LUTS and control the results by patient weight. Materials and Methods:The study comprised a cross-sectional analysis of 725 men included in a prostate cancer screening progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The combined effects of these may result in overexpression of toll-like receptors, transformation of prostatic cells into antigen-presenting cells, and up-regulation of growth factors (andromedins), leading to prostate enlargement. Among hormonal determinants of BPH, the majority of studies have reported sex steroid imbalances between total or free testosterone, dihydrotestosterone, estrogen, and progesterone levels [ 2 7 ], although their circulating levels did not necessarily reflect the causal relationship with prostatic volume and severity of LUTS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The combined effects of these may result in overexpression of toll-like receptors, transformation of prostatic cells into antigen-presenting cells, and up-regulation of growth factors (andromedins), leading to prostate enlargement. Among hormonal determinants of BPH, the majority of studies have reported sex steroid imbalances between total or free testosterone, dihydrotestosterone, estrogen, and progesterone levels [ 2 7 ], although their circulating levels did not necessarily reflect the causal relationship with prostatic volume and severity of LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these sex-steroid derangements, our results suggest that they may be also extended by changes in circulating DHEA-S and SHBG. Only a few studies in the literature have evaluated SHBG in patients with BPH, and the results have been inconsistent [ 7 10 ]. In our series, SHBG concentration was negatively associated with the prevalence of BPH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These concepts are reinforced by other studies that demonstrate that in obese men (body mass index [BMI] >25), only age, increasing total testosterone and sex score were related to their worsening LUTS. 40 …”
Section: Metabolic Syndrome Lower Urinary Tract Symptoms and Testostmentioning
confidence: 99%